2019
DOI: 10.1038/s41419-019-1556-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a master regulator of cell death and inflammation: molecular mechanisms and clinical implications for newborn care

Abstract: Melatonin, more commonly known as the sleep hormone, is mainly secreted by the pineal gland in dark conditions and regulates the circadian rhythm of the organism. Its intrinsic properties, including high cell permeability, the ability to easily cross both the blood–brain and placenta barriers, and its role as an endogenous reservoir of free radical scavengers (with indirect extra activities), confer it beneficial uses as an adjuvant in the biomedical field. Melatonin can exert its effects by acting through spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(194 citation statements)
references
References 146 publications
8
183
0
3
Order By: Relevance
“…This latter function can be both direct, due to melatonin's scavenger properties targeted in particular to mitochondria, or indirect through modulation of the expression of antioxidant enzymes [51][52][53]. In addition, melatonin has been shown to directly interact with target proteins modulating their function [4,54]. In our work, we first confirmed the expression of melatonin receptor MT1 in both primary and immortalized microglia.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This latter function can be both direct, due to melatonin's scavenger properties targeted in particular to mitochondria, or indirect through modulation of the expression of antioxidant enzymes [51][52][53]. In addition, melatonin has been shown to directly interact with target proteins modulating their function [4,54]. In our work, we first confirmed the expression of melatonin receptor MT1 in both primary and immortalized microglia.…”
Section: Discussionsupporting
confidence: 69%
“…Melatonin (5-methoxy-N-acetyltryptamine) is an endogenous neurohormone produced primarily by the pineal gland and mainly involved in the regulation of circadian rhythms. Aside from its classical 2 of 20 action on sleep/wake cycles, melatonin has largely been shown to be a pleiotropic molecule [1][2][3][4] with multiple beneficial actions. In agreement, animal studies have shown melatonin to be an effective neuroprotectant in a number of neurodegenerative conditions such as hypoxia/ischemia [5][6][7], Alzheimer's Disease [8], Parkinson's Disease [9], and spinal cord injury [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among all the antioxidants mentioned so far, melatonin plays a very important role in cardioprotection. Although melatonin is known to be a master regulator of cell death and inflammation [181], a few studies have reported its roles in inducing autophagy [182,183] and mitophagy during CVDs. In addition to the two studies mentioned in the "Atherosclerosis" and "Cardiomyopathies" sections [53,63], other studies have been conducted on ischemia and reperfusion conditions, during which mitochondrial fission is activated and the PTPC is in its open state [184].…”
Section: Targeting Mitophagy For Cardioprotectionmentioning
confidence: 99%
“…Melatonin is a hormone released by the pineal gland and regulates the sleep-wake cycle. It exerts antioxidant, anti-inflammatory, and antiapoptotic effects [114]. Recently, it has been demonstrated in a mouse model of AAN that treatment with melatonin protected mice against AA nephrotoxicity.…”
Section: Other Agentsmentioning
confidence: 99%